Comparação da Acurácia entre a Estimativa Clínica de Sobrevida e o Palliative Prognostic Index: o delírium interfere? - FERREIRA, Alyni Sebastiany Mendes (2022)
Introduction: The PPI scale is composed of five prognostic factors, among them the delirium symptom, which represents about 25% of the total score; the removal of this factor may be important for the outcome of the estimates. Clinical survival estimation offers a prognostic alternative that does not require invasive methods for patients, formulating prognoses through the professional's clinical experience. Incorrect estimates can result in poorer quality of life and increased health care costs. The prediction of survival for patients with advanced cancer and in palliative care directly impacts the clinical conduct of the multidisciplinary team and relativizes the approach to care. Objective: To analyze and compare the accuracy of the prognosis by the Palliative Prognostic Index (PPI) method, including the delirium symptom, and the Clinical Survival Estimate (CSS) in cancer patients in Palliative Care. Methodology: This is an analytical, observational, prospective cohort study, carried out with the analysis of quantitative data. The clinical survival estimate was performed by a Palliative Doctor and/or Oncologist through the ECS; the PPI was applied by the researchers who also filled out a sociodemographic form, without any communication between them. Patients with confirmed delirium symptoms had this data collected in medical records, since the hospital has its own protocol for the evaluation and diagnosis of delirium, CAM (Confusion Assessment Method) standard, considering the DMS-V criteria. Survival time was obtained by following patients admitted every 21 days, with serial predictions of ECS and PPI on the 42nd and 63rd day of hospitalization or until their death. Patients discharged from the hospital were followed up by repeated phone calls to the family according to the adopted protocol; survival was measured as the difference between the day of the first application of the PPI and ECS scale and the day of the patient's death. Results: The mean survival of patients was 37 days, in which 34 (29.3%) patients had a survival of less than 3 weeks with a confirmed diagnosis of delirium and 22 (19%) patients survived for more than 6 weeks without symptoms of delirium. . The first evaluation of the ECS showed an accuracy of 66.8%, a sensitivity of 65.5% and a specificity of only 58.6%. In the second evaluation, approximately 64.7% of accuracy, 60% of sensitivity, 64.7% of specificity were obtained. In the first assessment of the accuracy of the PPI scale, 65% of accuracy was identified, with 58.6% of sensitivity and 65.5% of specificity. In the second evaluation, the scale was 82.1% accurate, with a proportion of 90% sensitivity and 70.6% specificity. Conclusion: When comparing the PPI to the ECS exclusively in the evaluation of patients with delirium, it was possible to observe that this factor did not influence the accuracy of the prediction, however, when evaluating the population without delirium, it was observed that both predictors had an accuracy close to 70%. When comparing the clinical survival estimate and the PPI scale during the weekly assessments, it was found that only the PPI had satisfactory accuracy when applied in a serial methodology. In the evaluations by organic systems, it was understood that the two predictors had a good evaluation in the most prevalent, all with values well above 70%, confirming the superior performance of the PPI in the evaluation of the genitourinary system.